Sediment and Crustal Structure Beneath East Kalimantan and East Java, Indonesia From Receiver Function. Issue 1 (February 2021) - Bahri, Syaiful; Suryanto, Wiwit; Ngadmanto, Drajat
Abstract: We investigate the sediment and Earth's crustal structure beneath the East Kalimantan and East Java by modelling the stacked receiver function from six seismic broadband stations belong to the Meteorology, Climatology and Geophysics Agency of Indonesia (BMKG). The calculation of receiver functions from 60 teleseismic earthquake events using iterative time-domain deconvolution method. Inversion result shows a significant variation in the sediment layer thickness from 1 km to 4 km beneath East Java. It is correlated with the South East Java basinal area (station KRK) and the North East Java Basin (station GRJI and BWJI). The sediment layer of about 5 to 10 km beneath East Kalimantan is associated with the Kutai Basin (station SGKI, SMKI, and BKB). Average Sediment layer shear velocity (Vs) beneath all station is observed to be less than 2.31 km/s. Crustal thickness beneath East Java varies between 20 to 40 km and 34 to 50 km beneath East Kalimantan, with average crustal shear wave velocity, Vs 4.60 km/s.